EVALUATING THE PROFESSIONAL DUTIES OF CLASSROOM TEACHERS IN PRIMARY SCHOOLS - Latip, Asep Ediana (JMIE (Journal of Madrasah Ibtidaiyah Education), 2019)
The classroom teacher's professional duties are to educate, guide, teach, train, direct, judge and preserve. The problem is that many teachers are not professional in performing their duties has become a professional certificate, therefore the purpose of this study is the task of professional executive class teachers at the primary education education in Jakarta, Bogor, Depok, Tangerang dan Bekasi. The research method used is qualitative quantitative survey method because it is evaluative research. Data completion technique as evaluation research on professional task of classroom teacher at primary education in Jakarta, Bogor, Depok, Tangerang dan Bekasi is observation, interview, and document. The respondents of this research are classroom teachers at primary education in Jakarta, Bogor, Depok, Tangerang dan Bekasi. The benefits of this research are expected to provide theoretical and practical benefits to institutional governance on the development of teacher resources at the primary education level in Jakarta, Bogor, Depok, Tangerang dan Bekasi. The results showed that teachers in Jakarta, Bogor, Depok, Tangerang dan Bekasi perform their professional duties in designing a good learning plan with an average score of 72. Can perform professional duties at primary education level in aspects of learning activities very well with average score 87. And there is a difference in the implementation of professional tasks of certified class teachers with an average score of 73 scores, while unclassified grade teachers score an average of In the aspect of execution of professional duties in classroom teaching activities has not been certified has the advantage in performing professional tasks on aspects of learning activities at level primary education in Jakarta, Bogor, Depok, Tangerang dan Bekasi that is grade certified teacher average score 86,7, while class teacher have not certified result of score average 87,2.